A diketopyrrolopyrrole dye-based dyad on a porous TiO2 photoanode for solar-driven water oxidation. Issue 47 (25th September 2020) - Antón-García, Daniel; Warnan, Julien; Reisner, Erwin
Abstract : Construction of a water oxidising photoanode with an organic chromophore-catalyst dyad. Abstract : Dye-sensitised photoanodes modified with a water oxidation catalyst allow for solar-driven O2 evolution in photoelectrochemical cells. However, organic chromophores are generally considered unsuitable to drive the thermodynamically demanding water oxidation reaction, mainly due to their lack of stability upon photoexcitation. Here, the synthesis of a dyad photocatalyst (DPP-Ru ) consisting of a diketopyrrolopyrrole chromophore (DPPdye ) and ruthenium-based water oxidation catalyst (RuWOC ) is described. The DPP-Ru dyad features a cyanoacrylic acid anchoring group for immobilisation on metal oxides, strong absorption in the visible region of the electromagnetic spectrum, and photoinduced hole transfer from the dye to the catalyst unit. Immobilisation of the dyad on a mesoporous TiO2 scaffold was optimised, including the use of a TiCl4 pretreatment method as well as employing chenodeoxycholic acid as a co-adsorbent, and the assembled dyad-sensitised photoanode achieved O2 evolution using visible light (100 mW cm −2, AM 1.5G, λ > 420 nm). An initial photocurrent of 140 μA cm −2 was generated in aqueous electrolyte solution (pH 5.6) under an applied potential of +0.2 V vs. NHE. The production of O2 has been confirmed by controlled potential electrolysis with a faradaic efficiency of 44%. This study demonstrates that metal-free dyes are suitable light absorbers in dyadic systems for the assembly of water oxidising photoanodes.